Concentration, distribution, and characteristics of microplastic in estuary, coast and marine organisms in Indonesia: A Preliminary Review - Nurhana Rafika Sari; Azizah Intan Pangesty; Mochamad Chalid; Oman Zuas (Sekolah Tinggi Ilmu Pertanian Wuna, 2022)
There is a rising concern regarding the accumulation of microplastics (MPs) in the aquatic ecosystems. Monitoring effort is crucial to understand the concentration and distribution of MPs. The objective of this paper is to mapping the concentration and characteristics of MPs distributed/deposited in estuary, coast, sediment, and marine organism in Indonesia based on data published from the last five years. In the estuary and coast, the highest MPs concentration were located in Brantas River, East Java, around 133 - 5467 particles/m3. In sediment, the highly amount of MP’s, 1136 particles/kg, were found in Kawal village, Bintan Island, Riau. In marine organism, horn snail (Telescopium telescopium) from Rambut Island, Jakarta Bay contained the highest amount of MP’s around 764.81 particles/individual . MPs were commonly found in fragments, fibers, and films with size ranging between 1 μm - 5 mm. Those MPs are mostly made of polyethylene (PE), polypropylene (PP), polystyrene (PS) and polyesters (PES). The data summary obtained in this study could be useful for understanding the sources of MPs as well as monitoring the environmental condition in the aquatic ecosystems.